Influence of microhybrid resin and etching times on bleached enamel for the bonding of ceramic brackets - Leily Macedo Firoozmand; Juliana Viana Pereira Brandão; Melissa Proença Nogueira Fialho (Sociedade Brasileira de Pesquisa Odontológica, 2013)
The aim of this study was to evaluate the shear bond strength (SBS) of polycrystalline ceramic brackets (PCB) bonded after bleaching treatment using different composite resins and enamel etching times. A total of 144 bovine incisors were randomly divided into two study groups (n = 72, each) as follows: G1, enamel bleached with 35% hydrogen peroxide, and G2 (control group), enamel unbleached. After the bleaching treatment, the samples were stored in artificial saliva for 14 days. These groups were further divided into two subgroups (n = 36, each) as follows: GA, brackets bonded with Transbond XT (3M) and GB, brackets bonded with Filtek Z250 (3M). For each resin used, three different etching times with 37% phosphoric acid (15, 30 and 60 seconds) were tested. SBS tests were performed using a universal testing machine (EMIC), and the adhesive remnant index (ARI) score was verified. Significant differences among the three experimental conditions and interactions between the groups were observed. The type of composite resin accounted for 24% of the influence on the bond strength, whereas the etching time and bleaching treatment accounted for 14.5% and 10% of the influence on bond strength, respectively. The ARI revealed that the most common area of adhesion failure was at the composite resin-bracket interface. The type of composite resin, etching time and external bleaching significantly influenced the SBS of PCB on enamel, even after 14 days of saliva storage.